The Model of Self-realization Readiness Formation of Research Universities Students in the Process of Civic Education - Pugacheva, Natalya B.; Ezhov, Sergey G.; Kozhanov, Igor V.; Kozhanova, Marina B.; Ogorodnikova, Svetlana V.; Oshaev, Alexey G.; Timonin, Andrey I.; Goloshumova, Galina S. (International Review of Management and Marketing, 2016)
The relevance of the study is reasoned by the demand for professionals who are not only competitive in the labor market, but also possess civil position, ready for self-realization and construction of their own life in the flow of social transformation. The purpose of the article is to develop a knowledge-activities-model of readiness formation to self-realization of research universities students in the process of civic education. The leading method is the method of modeling, allowing consider the problem of research as a purposeful process of students' focus formation to choose the social role and civic position in the social and economic relations on the basis of understanding of their goals in life. The structure of the developed model includes a target (goal, objectives), methodological (the principles of integration, a participatory, continuity, multiculturalism), content (cognitive-oriented, project-case, civil-activities methods), organizational and procedural (including in educational content of educational material on the theory and practice of civil society; formation of information-event-learning environment; the development of teachers' methodological culture) and result (search activity, commitment and perseverance in achieving objectives, industriousness, readiness for independent decisions in a situation of choice, the responsibility for the choice of means to achieve the goal, awareness of their rights and obligations, duty and civic reliability) components. The model suggests the development of students' moral, legal and political focus based on personal-significant actions and it is also of practical value for teachers of research universities. Keywords: research universities, civic education, self-realization, moral and legal focus, personal and significant action. JEL Classifications: A22, I23, Z39